Comparison of Granulomatosis with Polyangiitis Clinical Features in Patients Depending on Involvement or Absence of Kidney Involvement - Puchala, Mateusz; Rydzewski, Andrzej; Kowalik, Ilona; Wisłowska, Małgorzata (Current Rheumatology Reviews, 2021)
Background: GPA is necrotizing inflammation of the small vessels with granulomas. Kidney involvement deteriorated its prognosis. Objective: Comparison of GPA patients with Kidney (KI) and without Kidney Involvement (nKI). Materials and Methods: We conducted a cross-sectional study of 50 consecutive adult GPA patients, 25 KI from Nephrology and 25 nKI from the Rheumatology Department of Central Clinical Hospital Ministry of Interior in Warsaw. We analyzed clinical features, organ involvement, laboratory, serological, imaging, histopathological data, BVAS and treatment. Results: The mean age of KI patients was statistically older than nKI (67.3±9.5 vs. 55.1±15.9, p=0.002). Generalized, severe, disease resistance was observed respectively in 92% vs. 44%, p<0.001. The number of red blood cells (3.47 vs. 4.41T/l, p<0.001), hemoglobin (10.0 vs. 12.9 g/dl, p<0.001) was lower in KI, higher mean serum creatinine (3.95 vs. 0.89 mg/dl, p<0.001), lower GFR (20.1 vs. 79.3, p<0.001), higher CRP (median: 43.4 vs. 2.0 mg/l, p<0.001), BVAS (16.6±4.4 vs. 10.1±6.2, p<0.001), c-ANCA (median: 119.0 vs. 15.2CU, p=0.017). Nodules in 28% KI, in 4% nKI (p=0.048) in chest X-ray, infiltration in 43.5% KI, in 15% nKI (p=0.042) in HRCT were observed. Skin granulomas were found in 61.5% nKI vs. 18.2% KI, (p=0.047). Renal biopsy revealed in KI patients focal segmental glomerulonephritis in 11.8%, crescentic glomerulonephritis in 17.6%, and pauci-immune crescentic glomerulonephritis in 70.6%. Conclusion: In patients with KI we found generalized, severe, resistant GPA, higher BVAS more frequently than inpatients without KI. The results of laboratory parameters were worse in patients with KI. Aggressive immunosuppressive treatment is often used in the KI group.
Keywords: induction therapy